Impact of the Duration of Postoperative Antibiotics on the Prognosis of Patients with Infective Endocarditis - Jinnam Kim; Jung Ho Kim; Hi Jae Lee; Se Ju Lee; Changhyup Kim; Jung Ah Lee; Ki Hyun Lee; Won Kyung Pyo; Jin Young Ahn; Su Jin Jeong; Nam Su Ku; Seung Hyun Lee; et al. (MDPI AG, 2023)
Appropriate postoperative antibiotic treatment in patients with infective endocarditis (IE) reduces the risks of recurrence and mortality. However, concerns about adverse drug reactions arise due to prolonged antibiotic usage. Therefore, we compared the recurrence and mortality rates according to the duration of postoperative antibiotic therapy in patients with IE. From 2005 to 2017, we retrospectively reviewed 416 patients with IE treated at a tertiary hospital in South Korea; among these, 216 patients who underwent heart valve surgery and received appropriate antibiotics were enrolled. The patients were divided into two groups based on the duration of usage of postoperative antibiotic therapy; the duration of postoperative antibiotic therapy was more than two weeks in 156 patients (72.2%) and two weeks or less in 60 patients (27.8%). The primary endpoint was IE relapse. The secondary endpoints were 1-year IE recurrence, 1-year mortality, and postoperative complication rates. The median age was 53 (interquartile range: 38-62) years. The relapse rate of IE was 0.9% (2/216). There was no statistical difference in relapse (0.0% vs. 1.3%, p = 0.379), 1-year recurrence (1.7% vs. 1.3%, p = 0.829), or 1-year mortality (10.0% vs. 5.8%, p = 0.274) between patients with postoperative antibiotic administration of two weeks or less versus more than two weeks. The duration of postoperative antibiotic therapy did not affect the 1-year mortality rate (log-rank test, p = 0.393). In conclusion, there was no statistically significant difference in recurrence, mortality, or postoperative complications according to the duration of postoperative antibiotic therapy.